Peningkatan Kinerja Kelompok Usaha Pengolahan Ikan Air Tawar di Kabupaten Sleman - Wiwit Rahayu; Sri Marwanti; Agustono Agustono; Minar Ferichani; Refa'ul Khairiyakh; Indah Nurhidayati (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Freshwater fish farming is one of the efforts made by the people of Sindumartani Village, Ngemplak Sub-district, Sleman Regency. The battle for water and land has made most people cultivate freshwater fish, especially tilapia. This makes fish products abundant. This condition is the initiative of the Mina Mandiri Women Farmer Group to process the fish production into several processed fish products such as fish chips and shredded fish. One of the obstacles faced in the effort to develop this processing business is that the group's performance has not been optimal due to a lack of knowledge about group business interests and how to create a solid group with good performance. This community service is carried out in order to solve these problems by conducting group dynamics training both in theory and practice. The group dynamics training that was carried out made women members of the Mina Mandiri Women Farmer Group understand the importance of group business, the factors that are the strengths and weaknesses of groups and working in groups (teamwork). The understanding and skills obtained from community service activities increase the group's performance. This can be seen from the increasing number of members who attend monthly meetings, the increasing frequency of production activities, the increasing types of processed fish products and the wider the marketing area.